2011
DOI: 10.1103/physreva.84.033610
|View full text |Cite
|
Sign up to set email alerts
|

Cold-atom gravimetry with a Bose-Einstein condensate

Abstract: We present a cold-atom gravimeter operating with a sample of Bose-condensed 87 Rb atoms. Using a Mach-Zehnder configuration with the two arms separated by a two-photon Bragg transition, we observe interference fringes with a visibility of (83 ± 6)% at T = 3 ms. We exploit large momentum transfer (LMT) beam splitting to increase the enclosed space-time area of the interferometer using higher-order Bragg transitions and Bloch oscillations. We also compare fringes from condensed and thermal sources and observe a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
132
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 24 publications
0
132
0
Order By: Relevance
“…The probe and control beams are detuned from the excited state |3 by an amount p = ω 3 − ω p and c = ω 3 − ω 2 − ω c , respectively. sample, since it is generally optimal for atom interferometry to operate in a regime where the interatomic interactions are negligible [45,[56][57][58]. Under these approximations and the rotating-wave approximation [59], the Hamiltonian for the system becomeŝ…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
See 1 more Smart Citation
“…The probe and control beams are detuned from the excited state |3 by an amount p = ω 3 − ω p and c = ω 3 − ω 2 − ω c , respectively. sample, since it is generally optimal for atom interferometry to operate in a regime where the interatomic interactions are negligible [45,[56][57][58]. Under these approximations and the rotating-wave approximation [59], the Hamiltonian for the system becomeŝ…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…We explicitly consider Bose-condensed atomic sources, as the narrow velocity distribution and large coherence length of a Bose-Einstein condensate (BEC) offers considerable advantages over thermal sources, including more precise manipulation of the motional state, increased visibility, and the prospect of feedback stabilization under high flux outcoupling [45][46][47][48][49][50][51]. However, many of the results in this paper are equally applicable to ultracold thermal sources.…”
Section: Introductionmentioning
confidence: 99%
“…Although most state-of-the-art atom interferometers currently utilize laser cooled atoms, there may be some benefit to using Bose-Einstein-condensed atoms. Bose-Einstein-condensed atoms provide improved visibility in configurations which require complex manipulation of the motional state, such as high-momentum-transfer beam splitters [9]. The ultimate limit of the sensitivity of any interferometric device which uses uncorrelated particles in each arm is the standard quantum limit φ = 1 √ N t , where N t is the total number of detected particles [10].…”
Section: Introductionmentioning
confidence: 99%
“…13 It is shown that coherent wave-packet splitters, with multi-photon momentum transfer, can significantly increase the space-time area. 14,15 Recently, some experiments have achieved multiphoton momentum transfer by means of Bragg transitions, [16][17][18][19] which is an effective way to improve the sensitivity of an atom interferometer.…”
Section: Introductionmentioning
confidence: 99%